Examination of concept maps studies in terms of bibliometric features - Polatcan, Faruk; Coban, Ismail; Er, Onur (Geomatik Journal, 2025)
Concept maps are visuals that present the relationships between concepts on a hierarchical level. This hierarchical order is expected to be more easily adopted by learners. The aim of this study is to systematically analyze the studies on concept maps in Web of Science (WoS). For this purpose, bibliometric characteristics such as type of publication, language of publication, most cited publications, keywords, productive institutions and countries were analyzed for studies on concept maps between 1979 and 2025. The descriptive design of the quantitative method was used in the study. Map networks were created with the VOSviewer program from the data compiled with the keyword concept maps in the WoS database. The results of the research show that concept maps are a powerful tool to increase knowledge retention and transfer in learning processes. Another result obtained from concept maps research is that linguistic and cultural influences have an expanding or limiting effect on scientific studies.
Keywords: Concept Maps; Bibliometrics; Bibliometric Analysis; VOSviewer